Factors Related to the Incidence of Typhoid Fever in the Work Area Health Office of Jayawijaya Regency - Ura, Rahmad Suryawan; Peristiowati, Yuly (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2021)
Typhoid fever is a disease that is prone to occur in Indonesia, because of the characteristics of the climate that is very prone to diseases related to the seasons. The purpose of this study is to analyze factors related to the incidence of typhoid fever in the Working Area of the Jayawijaya District Health Office. The research design used is quantitative analytics method using quantitative data. The type of approach used is case control. The population is 74 patients with typhoid fever. The large sample taken as many as 37 respondents, with a large comparison of samples between the number of respondents in the case group is 37 respondents, and 37 respondents as a control group, so the total number of samples is 74 respondents. Sampling techniques used in this study is a simple random sampling technique. Based on the results of the study, it is known that there is no relationship between age and the incidence of typhoid fever in the Working Area of the Jayawijaya District Health Office. Chi-square test result obtained p-Value Sig (0.445) > α (0.05). While it is known that there is a relationship between the level of knowledge, the level of education, hygiene of individual respondents with the incidence of typhoid fever in the Work Area of the Health Office of Jayawijaya Regency. Chi-square test results obtained p- value (0.000) < α (0.05) and environmental sanitation with the incidence of Typhoid Fever in the Work Area of the Jayawijaya District Health Office. Chi-square test result obtained p-value (0.001) < α (0.05). Based on the results of the study is expected to increase kinship with patients as well as by providing health services visits to the patient's home.